Childhood interleukin-6, C-reactive protein and atopic disorders as risk factors for hypomanic symptoms in young adulthood: a longitudinal birth cohort study. Issue 1 (1st August 2016) - Hayes, J. F.; Khandaker, G. M.; Anderson, J.; Mackay, D.; Zammit, S.; Lewis, G.; Smith, D. J.; Osborn, D. P. J.
Abstract : Background: There are no existing longitudinal studies of inflammatory markers and atopic disorders in childhood and risk of hypomanic symptoms in adulthood. This study examined if childhood: (1) serum interleukin-6 (IL-6) and C-reactive protein (CRP); and (2) asthma and/or eczema are associated with features of hypomania in young adulthood. Method: Participants in the Avon Longitudinal Study of Parents and Children, a prospective general population UK birth cohort, had non-fasting blood samples for IL-6 and CRP measurement at the age of 9 years ( n = 4645), and parents answered a question about doctor-diagnosed atopic illness before the age of 10 years ( n = 7809). These participants completed the Hypomania Checklist at age 22 years ( n = 3361). Results: After adjusting for age, sex, ethnicity, socio-economic status, past psychological and behavioural problems, body mass index and maternal postnatal depression, participants in the top third of IL-6 values at 9 years, compared with the bottom third, had an increased risk of hypomanic symptoms by age 22 years [adjusted odds ratio 1.77, 95% confidence interval (CI) 1.10–2.85, p < 0.001]. Higher IL-6 levels in childhood were associated with adult hypomania features in a dose–response fashion. After further adjustment for depression at the age of 18 years this association remained (adjusted odds ratio 1.70, 95% CI 1.03–2.81, p = 0.038). There was no evidence of an association of hypomanic symptoms with CRP levels, asthma or eczema in childhood. Conclusions: Higher levels of systemic inflammatory marker IL-6 in childhood were associated with hypomanic symptoms in young adulthood, suggesting that inflammation may play a role in the pathophysiology of mania. Inflammatory pathways may be suitable targets for the prevention and intervention for bipolar disorder.